2009
DOI: 10.1007/s10067-009-1125-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a high-intensity exercise program in patients with rheumatoid arthritis

Abstract: The aims of this study were to describe rheumatoid arthritis patients' compliance with continued exercise after participation in a 2-year supervised high-intensity exercise program and to investigate if the initially achieved effectiveness and safety were sustained. Data were gathered by followup of the participants who completed the 2-year high-intensity intervention in a randomized controlled trial (Rheumatoid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
0
42
0
6
Order By: Relevance
“…However, it appears that the benefits of PRT, once established (i.e., after 8 -12 weeks of training), can be maintained with reduced training. In the Rheumatoid Arthritis Patients in Training study (11), gains in KES following 2 years of twice weekly HI training (including strength training) were maintained by those patients who continued exercising once per week for the subsequent 18 months, but completely lost by those who stopped exercising. Similarly, substantial retention of gains in strength and function following 6 months (12) and 2 years (13) of HI PRT is reported for RA patients who remained very physically active over the subsequent 3 years, i.e., performing on average 4 bouts of moderate-intensity to HI aerobic exercise per week (e.g., walking, cycling, cross-country skiing) and, in the latter study, not reducing the time spent exercising (4 hours/week) and often continuing strength training.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that the benefits of PRT, once established (i.e., after 8 -12 weeks of training), can be maintained with reduced training. In the Rheumatoid Arthritis Patients in Training study (11), gains in KES following 2 years of twice weekly HI training (including strength training) were maintained by those patients who continued exercising once per week for the subsequent 18 months, but completely lost by those who stopped exercising. Similarly, substantial retention of gains in strength and function following 6 months (12) and 2 years (13) of HI PRT is reported for RA patients who remained very physically active over the subsequent 3 years, i.e., performing on average 4 bouts of moderate-intensity to HI aerobic exercise per week (e.g., walking, cycling, cross-country skiing) and, in the latter study, not reducing the time spent exercising (4 hours/week) and often continuing strength training.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although caution is advocated with regard to high-intensity exercise prescription because of possible injury and relapse in individuals with RA, some studies have shown that patients with moderate disease may be able to tolerate high-intensity exercise. 23,42 In a recent study by De Jong et al on the longterm effects of a high-intensity exercise programme, it was found that there were no detrimental effects on disease activity or radiological damage of the large joints. 42 The duration of the exercise session is highly variable and can be manipulated with respect to intensity to provide the desired exercise stimulus 4 (Table I).…”
Section: Physical Activity Levels Of Patients With Rheumatoid Arthritismentioning
confidence: 99%
“…23,42 In a recent study by De Jong et al on the longterm effects of a high-intensity exercise programme, it was found that there were no detrimental effects on disease activity or radiological damage of the large joints. 42 The duration of the exercise session is highly variable and can be manipulated with respect to intensity to provide the desired exercise stimulus 4 (Table I).…”
Section: Physical Activity Levels Of Patients With Rheumatoid Arthritismentioning
confidence: 99%
“…Following on from moderate to high intensity progressive resistance training (PRT) or combined programs, RA patients have been shown to have high adherence rates to exercise in "real life" situation that help maintain improvements [61]. Although, continuation of both high-intensity and high-frequency sessions may be required for maintenance of training gains in aerobic fitness, muscle strength, and functional ability [62], but evidence is still required regarding the minimum maintenance regimen. Home-based exercise programs have also been investigated and have been shown to improve quality of life and functional status [63].…”
Section: Physical Activity Prevents Rheumatoid Cachexiamentioning
confidence: 99%
“…Even so, strengthening exercises are recommended for all stages of RA [66]. Exercise programs, even over long periods and at high intensities, have been found to be safe as well as effective [62]. However, little is known as to whether exercise, particularly strength training, should be continued through inflammatory "flares" and further research should be conducted on the effects of exercise on joints that are already severely damaged.…”
Section: Physical Activity Prevents Rheumatoid Cachexiamentioning
confidence: 99%